Small signal stability analysis of dynamic power system consisting of double synchronous generators connected to infinite bus - Taşar, B.; Özdemir, M. (My University, 2012)
In this study, it has been analyzed the stability of a dynamic system consist of double synchronous generators connected to infinite power bus against small signal disturbances which is low amplitude and low frequency. In the literature, many simplified models with different degree of synchronous generator have been proposed and used for studying the dynamic stability of power systems. The most widely one is third order model of Synchronous Generator connecting to Infinite Power Bus (SGIPB) in which are taken into consideration both rotor dynamics and stator dynamics but are neglected the affect of damping windings, the stator winding resistance and the stator flux variation. In this study; t-model of synchronous generator has been generated without neglecting stator resistant and stator flux variation as different from other studies in the literature and a dynamic model of double synchronous generators infinite bus system(DSGIB) has been simulated in Matlab/Simulink environment. On the other hand, Conventional Power System Stabilizer (CPSS) is designed by using the linearized model to increase the stability of synchronous generator. In this case, the system exhibits performance loses when the operating point have change. In this study, in order to get rid of the disadvantage, a Fuzzy logic based Power System Stabilizer (FPSS) having a robust structure has been additionally designed, which the loss of performance is not seen even if system parameters such as operation point and line impedance of the power system change. In the simulations, the performances across the small signal disturbance of the proposed FPSS system has been compared to those of CPSS system and the system including only Automatic Voltage Regulator (AVR).
Sonsuz güçlü baraya ba?li çi?ft senkron jeneratörden oluşan di?nami?k si?stemi?n küçük i?şaret kararlilik anali?zi?
Keywords: AVR; CPSS; Fuzzy logic control; Power system stability; Small signal stability